Passenger satisfaction and decision of repurchasing on rail transportation services - Venny Arianti; Yosi Pahala; Aswanti Setyawati; Prasadja Ricardianto (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
The purpose of the study was to determine and analyze the effect of train rates, comfort and timeliness on passenger satisfaction and the impact of repurchase decision of train transportation services for the Jenggala Train on the Sidoarjo-Mojokerto route, at East Java, Indonesia. The main problem, there are complaints about unsatisfactory service, inaccuracy of departure and arrival time at the station aim. Also, the passenger capacity provided is large, but the volume transport is still minimal and there is no data on passengers who make repeat purchases. The sample are 100 Jenggala train crossing service Sidoarjo-Mojokerto passengers. Method of data analyze used path analysis. The result showed that the changes of rate amount, experience of passenger comfort, and timeliness of train travel had major impact on the decision of repurchase. As a theorithical and practical implication, the improvement of service user facilities at the station and on the train is very important needed to create comfort for users of transportation services train, because the comfort variable has a significant effect dominant in influencing purchasing decisions.